Weak central coherence in weight‐restored adolescent anorexia nervosa: Characteristics and remediation. Issue 8 (28th March 2017) - Weinbach, Noam; Perry, Amit; Sher, Helene; Lock, James D.; Henik, Avishai
Abstract: Objective: Weak central coherence (WCC) refers to a bias towards processing details (local processing) at the expense of paying attention to the bigger picture (global processing). Multiple studies reported WCC in adults with anorexia nervosa (AN). Evidence for WCC in adolescents with AN has been inconsistent. The current study characterizes WCC in weight‐restored adolescents with AN (WR‐AN) using a direct measure of WCC, and examines whether WCC can be remediated by increasing alertness level—a manipulation that was found useful in enhancing global processing in healthy individuals and clinical populations. Methods: 40 adolescents (18 WR‐AN and 22 healthy adolescents) performed a global/local processing task (Navon task). Auditory alerting cues that elevate alertness level were integrated into the task. Results: Both groups processed global information faster than local information. However, compared with controls, adolescents with WR‐AN were better at ignoring an irrelevant bigger picture while attending to details (smaller global interference) and had greater difficulty ignoring irrelevant details while attending to the bigger picture (larger local interference). These differences were attenuated when adolescents with WR‐AN were under a state of high alertness. Additionally, the local interference effect was positively correlated with three independent self‐report questionnaires assessing eating disorders symptomatology. Discussion: This study suggests that abnormal interference by irrelevant global and local information is a central characteristic of WCC in adolescents with WR‐AN that cannot be accounted for by enduring illness or malnourishment. Additionally, this study demonstrates that WCC can be temporarily remediated by encouraging a state of high alertness.